Pengaruh Profitabilitas Leverage dan Kebijakan Dividen Terhadap Nilai Perusahaan Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Adnan, Anang Wahyudi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research examines the effect of profitability, leverage and dividend policy to enterprise value of agricultural sector listed on Indonesian stock exchange. The research type is associative with quantitative approach. The sampling metode is purposive sampling which resulted 12 samples of company from 2018-2022 period. To answer the hypothesis in this research used multiple linear regression of panel data that analys with E-Views version 12. This research findings show that profitability (return on equity) have significant and positive effects on enterprise value. Whereas leverage (debt to equity ratio) and dividend policy (dividend payout ratio) doesn’t have effects on enterprise value. In investation need to be noticed carefuly for analys the performance from a company by seeing the value of profitability, leverage and dividend policy for increase enterprise value so able to give the advantage for the investor or stakeholders.